Digital Green Banking Adoption and Sustainable Consumer Behaviour: A Systematic Review - Joseph, Dina; Vetrivel, M. (International Journal of Aquatic Research and Environmental Studies, 2026)
Digital green banking has emerged as an important pathway through which financial institutions can integrate digital transformation with environmental sustainability and influence consumer behaviour. This systematic literature review synthesizes evidence on digital green banking adoption and sustainable consumer behaviour. Following PRISMA 2020 guidelines, relevant studies published between 2016 and 2026 were identified through scholarly databases, publisher platforms, and manual screening. From 270 initially identified records, 25 studies met the eligibility criteria and were included in the final synthesis. The review shows that digital green banking adoption is shaped by customer trust, awareness, perceived environmental value, satisfaction, green image, behavioural willingness, and environmental consciousness. Digital banking channels and green FinTech platforms enhance the accessibility and visibility of sustainability-oriented financial services, while green financial products connect consumer financial decisions with broader sustainable consumption practices. The findings also indicate that customers are more likely to adopt digital green banking services when green claims are credible, services are convenient, and environmental benefits are clearly communicated. However, the literature remains fragmented, with limited evidence on actual usage behaviour, longitudinal adoption patterns, and measurable environmental outcomes. This review highlights the need for integrated theoretical models and stronger empirical evidence to understand how digital green banking can promote sustained consumer engagement and responsible financial behaviour.
Keywords: Digital green banking; Green banking adoption; Green FinTech; Sustainable consumer behaviour; Green financial products; Customer trust